Titanium silicalite molecular sieve as well as preparation method and application thereof
By using template agents with specific structures and hydrothermal crystallization treatment technology, the lipophilicity of titanium silicon molecular sieve is improved, and the problem of strong hydrophilicity when catalyzing macromolecular hydrocarbons is solved, and higher catalytic performance is achieved.
Patent Information
- Application Number
- CN202310956311.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-31
AI Technical Summary
Existing titanium-silicon molecular sieves show strong hydrophilicity when catalyzing the conversion of macromolecular hydrocarbons, resulting in a degradation of catalytic performance.
The first template agent and the second template agent having a specific structure are used as the composite template agent, and the lipophilicity of the titanium silicon molecular sieve is improved by hydrothermal crystallization treatment.
The catalytic performance of titanium silicon molecular sieve is improved and the conversion capacity of macromolecular hydrocarbons is enhanced.
Smart Images

Figure CN119430216A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of inorganic material preparation, and in particular, to a titanium silicon molecular sieve and a preparation method and application thereof. Background Art
[0002] Titanium silicate molecular sieve refers to a type of heteroatom molecular sieve containing skeleton titanium. The microporous titanium silicate molecular sieves synthesized so far include TS-1 (MFI structure), TS-2 (MEL structure), Ti-Beta (BEA structure), Ti-ZSM-12 (MTW structure) and Ti-MCM-22 (MWW structure), and the mesoporous titanium silicate molecular sieves include Ti-MCM-41 and Ti-SBA-15. The development and application of titanium silicate molecular sieves have successfully expanded the zeolite molecular sieve from the acid catalysis field to the catalytic oxidation field, which is of milestone significance. Among them, TS-1, first announced by the Italian Enichem Company in 1983, is the most representative titanium silicate molecular sieve. TS-1 has an MFI topological structure and a two-dimensional ten-membered ring channel system. Its
[100] direction is a straight channel with a pore size of 0.51×0.55nm, and the
[010] direction is a sinusoidal channel with a pore size of 0.53×0.56nm. Due to the introduction of Ti atoms and its special pore structure, the oxidation system composed of TS-1 and H2O2 has the advantages of mild reaction conditions, green oxidation process and good selectivity of oxidation products in the oxidation reaction of organic matter. At present, this catalytic oxidation system can be widely used in reactions such as alkane oxidation, olefin epoxidation, phenol hydroxylation, ketone (aldehyde) ammoximation and oil oxidative desulfurization. Among them, industrial applications have been successively realized in phenol hydroxylation, ketone (cyclohexanone, butanone, acetone) ammoximation and propylene epoxidation.
[0003] Titanium silicate molecular sieve TS-1 is the most widely used titanium-containing molecular sieve at present. Its pore size is about 0.56nm, and it has a unique confinement and shape-selective effect in the conversion of low-molecular hydrocarbons. However, due to the limitation of pore size, its conversion ability for large molecular hydrocarbons is relatively weak.
[0004] Ti-containing heteroatom molecular sieves have a large number of silanol defects inside and are highly hydrophilic. When reacting with aqueous hydrogen peroxide solution as an oxidant, they easily adsorb water molecules and form a hydrophilic environment in the pores, which hinders the adsorption, diffusion and reaction of organic reaction molecules and seriously affects the catalytic performance of the molecular sieve. Summary of the invention
[0005] The purpose of the present disclosure is to provide a titanium silicate molecular sieve and a preparation method and application thereof, so as to effectively enhance the lipophilicity of the titanium silicate molecular sieve and improve the catalytic performance of the molecular sieve.
[0006] In order to achieve the above object, the present disclosure provides a method for preparing titanium silicon molecular sieve in a first aspect, comprising the following steps:
[0007] S1, contacting a silicon source, a titanium source, a composite template and water to obtain a raw material mixture; wherein the composite template comprises a first template and a second template; the first template is selected from one or more compounds having a structure shown in the following formula (1); the second template is selected from one or more compounds having a structure shown in the following formula (2):
[0008]
[0009] In formula (1), R1, R2, R3 and R4 are each independently selected from an alkyl group having 2 to 5 carbon atoms or an alkenyl group having 2 to 5 carbon atoms;
[0010] In formula (2), R5, R6 and R7 are each independently selected from an alkyl group having 2 to 5 carbon atoms or an alkenyl group having 2 to 5 carbon atoms; R8 is selected from an aryl group having 6 to 12 carbon atoms;
[0011] S2. subjecting the raw material mixture to a first hydrothermal crystallization treatment.
[0012] Optionally, in the first template formula (1), R1, R2, R3 and R4 are each independently selected from an alkyl group having 3 carbon atoms or an alkenyl group having 3 carbon atoms; optionally, the first template is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, butyltripropylammonium hydroxide, 1-butenyltripropylammonium hydroxide, 2-butenyltripropylammonium hydroxide and 3-butenyltripropylammonium hydroxide; preferably, it is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, butyltripropylammonium hydroxide and 1-butenyltripropylammonium hydroxide;
[0013] Optionally, in the second template agent formula (2), R5, R6 and R7 are each independently selected from an alkyl group having 2 to 4 carbon atoms or an alkenyl group having 2 to 4 carbon atoms; R8 is selected from an aryl group having 6 to 8 carbon atoms; preferably, R5, R6 and R7 are each independently selected from an alkyl group having 3 carbon atoms or an alkenyl group having 3 carbon atoms; R8 is selected from a group having 6 to 8 carbon atoms and containing a phenylene group; optionally, the second template agent is selected from phenyl tripropyl ammonium hydroxide, p-tolyl tripropyl ammonium hydroxide, p-ethylphenyl tripropyl ammonium hydroxide, benzyl tripropyl ammonium hydroxide, phenethyl tripropyl ammonium hydroxide, phenyl allyl dipropyl benzene The invention relates to one or more of p-tolyl allyl dipropyl ammonium hydroxide, p-ethylphenyl allyl dipropyl ammonium hydroxide, benzyl allyl dipropyl ammonium hydroxide, phenethyl allyl dipropyl ammonium hydroxide, phenyl allyl dipropyl ammonium hydroxide, p-tolyl allyl dipropyl ammonium hydroxide, p-ethylphenyl allyl dipropyl ammonium hydroxide, benzyl allyl dipropyl ammonium hydroxide and phenethyl allyl dipropyl ammonium hydroxide; preferably, it is one or more selected from phenyl tripropyl ammonium hydroxide, p-tolyl tripropyl ammonium hydroxide, phenyl allyl dipropyl phenyl ammonium hydroxide, benzyl allyl dipropyl ammonium hydroxide and phenyl allyl dipropyl ammonium hydroxide.
[0014] Optionally, the silicon source is selected from at least one of organic silicone grease, solid silica gel, white carbon black and silica sol; preferably, it is selected from at least one of organic silicone grease, solid silica gel and white carbon black;
[0015] Optionally, the organic silicone grease is selected from one or more compounds having a structure represented by the following formula (A):
[0016]
[0017] R a , R b , R c and R d Each is independently selected from an alkyl group having 1 to 4 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, the R a , R b , R c and R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl; further preferably, the organic silicone grease is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicate; further preferably, it is selected from one or more of tetramethyl silicate, tetraethyl silicate and dimethyl diethyl silicate;
[0018] Optionally, the titanium source is selected from one or more of an organic titanium source and an inorganic titanium source;
[0019] Preferably, the organic titanium source is a titanium-containing organic acid ester, selected from at least one of the structures represented by the following formula (B):
[0020]
[0021] Where R e , R f , R g and R h are each selected from an alkyl group having 1 to 6 carbon atoms, preferably a straight-chain alkyl group having 1 to 4 carbon atoms and a branched-chain alkyl group having 3 to 6 carbon atoms, and more preferably R e , R f , R g and R h are independently selected from a straight chain alkyl group having 2 to 4 carbon atoms and a branched chain alkyl group having 2 to 4 carbon atoms; optionally, R e , R f , R g and R h Each of the following groups is independently selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl and isohexyl; preferably each of the following groups is independently selected from one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl;
[0022] Preferably, the inorganic titanium source is selected from one or more of chloride, nitrate or sulfate of titanium;
[0023] Further preferably, the titanium source is selected from one or more of titanium tetrachloride, titanium sulfate, titanium nitrate, tetraethyl titanate, tetrapropyl titanate and tetrabutyl titanate.
[0024] Optionally, in step S1, the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): composite template: water is 1: (0.001-0.040): (0.05-0.30): (5-40); preferably 1: (0.010-0.035): (0.10-0.20): (10-30);
[0025] Preferably, in the composite template, the molar ratio of the first template to the second template is 1:(0.01-0.10), preferably 1:(0.02-0.08), and more preferably 1:(0.03-0.08).
[0026] Optionally, step S1 further comprises the step of hydrolyzing and removing alcohol from the raw material mixture;
[0027] Optionally, the conditions for the hydrolysis and alcohol removal treatment include: treating at 5-120° C. for 0.5-48 h; preferably treating at 50-100° C. for 1-24 h, and more preferably treating at 60-90° C. for 5-20 h.
[0028] Optionally, in step S2, the conditions of the first hydrothermal crystallization treatment include: a hydrothermal crystallization temperature of 150 to 200°C, a hydrothermal crystallization time of 2 to 168 hours, and a hydrothermal crystallization pressure of autogenous pressure; preferably, the hydrothermal crystallization temperature is 160 to 190°C, and the hydrothermal crystallization time is 4 to 80 hours; further preferably, the hydrothermal crystallization temperature is 165 to 188°C, and the hydrothermal crystallization time is 5 to 40 hours.
[0029] Optionally, the method further comprises: drying and / or calcining the crystallized product obtained by the first hydrothermal crystallization treatment to obtain a solid product;
[0030] Optionally, the drying conditions include: a drying temperature of 100 to 200° C. and a drying time of 2 to 10 hours;
[0031] The conditions for the calcination treatment include: a calcination temperature of 350-650° C. and a calcination time of 2-10 hours; preferably, a calcination temperature of 450-550° C. and a calcination time of 3-8 hours.
[0032] Optionally, the method further comprises: contacting the solid product with an acid solution to perform an acid solution treatment, and then adding a pH regulator to perform a neutralization treatment to obtain an intermediate product;
[0033] Optionally, in the acid treatment, the acid is selected from one or more of hydrochloric acid, nitric acid, phosphoric acid, carbonic acid, sulfuric acid and acetic acid; the acid concentration is 0.1-1.0 mol / L, and the mass volume ratio of the acid to the solid product is 80-150 g solid product / 1 L acid; Optionally, the conditions of the acid treatment include: contact temperature of 50-150° C., preferably 60-100° C., contact time of 0.5-5.0 h, preferably 1.0-3.5 h;
[0034] Optionally, the pH adjuster is selected from one or more alkali solutions; the alkali solution is selected from one or more of ammonia water, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate and sodium bicarbonate, and the neutralization treatment adjusts the pH value of the solution to 5-7.
[0035] Optionally, the method further comprises: mixing the intermediate product with a third template and performing a second hydrothermal crystallization treatment;
[0036] Optionally, the mass ratio of the intermediate product to the third template is 2 to 20:1; preferably 5 to 15:1; the conditions of the second hydrothermal crystallization treatment include: a hydrothermal crystallization temperature of 150 to 200°C, a hydrothermal crystallization time of 10 to 40 hours, and a hydrothermal crystallization pressure of autogenous pressure; preferably, the hydrothermal crystallization temperature is 160 to 180°C, and the hydrothermal crystallization time is 20 to 30 hours;
[0037] Optionally, the third template is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide and butyltripropylammonium hydroxide.
[0038] A second aspect of the present disclosure provides the titanium silicate molecular sieve according to the first aspect.
[0039] The third aspect of the present disclosure provides a titanium silicon molecular sieve having the following infrared hydroxyl spectrum characteristics: the infrared hydroxyl spectrum of the titanium silicon molecular sieve is 3200-3800 cm -1 The peak area calculated by normalization of the characteristic peak within the wavenumber range is recorded as I1, and I1 is 1.35 to 6.55, preferably any value between 1.35 and 5.38, and more preferably any value between 3.03 and 5.05. The normalization refers to deducting the baseline from the measured infrared hydroxyl spectrum, integrating the peak area and dividing it by the sample mass to obtain the infrared hydroxyl peak area value per unit mass of the sample.
[0040] Optionally, the molar ratio of silicon atoms to titanium atoms in the titanium silicon molecular sieve is 10 to 100:1, preferably 20 to 50:1;
[0041] Optionally, the average particle size of the molecular sieve particles of the titanium silicate molecular sieve is 0.10 to 0.50 μm, preferably 0.20 to 0.40 μm; the BET specific surface area is 400 to 500 m 2 / g, preferably 430 to 470 m 2 / g; micropore specific surface area is 350~450m 2 / g, preferably 380 to 410 m 2 / g; total pore volume is 0.20~0.50cm 3 / g, preferably 0.30 to 0.40 cm 3 / g; mesopore volume is 0.03~0.30cm 3 / g, preferably 0.15 to 0.25 cm 3 / g;
[0042] Optionally, the titanium silicalite molecular sieve has an AEL, AFI, AFN, BEC, CFI, CHA, CON, EUO, FAU, FER, IMF, LTA, MER, MFI, MEL, MOR, MWW, RHO, TON, *BEA, *EWT or a two-dimensional hexagonal phase structure; preferably, it has an MFI structure.
[0043] The fourth aspect of the present disclosure provides the use of the titanium silicon molecular sieve described in the second aspect and the third aspect of the present disclosure in the catalytic oxidation reaction and / or adsorption separation process of organic matter.
[0044] The organic catalytic reaction includes olefin epoxidation to prepare epoxy compounds, olefin chlorohydrinization to prepare chlorohydrin, aldehyde / ketone ammoximation to prepare aldehyde / ketone oxime and ketone Beckmann rearrangement to prepare amide;
[0045] Optionally, the organic catalytic reaction is cyclohexanone ammoximation, comprising the following steps:
[0046] Under oximation reaction conditions, cyclohexanone, an oxidant, ammonia and a catalyst are contacted to carry out an oxidation reaction; the catalyst comprises the titanium silicon molecular sieve;
[0047] Optionally, the oxidant is selected from one or more of hydrogen peroxide, tert-butyl hydroperoxide, cumene hydroperoxide and m-chloroperbenzoic acid; preferably, the reaction is carried out in the presence of a solvent; the solvent is selected from one or more of n-butanol, tert-butanol, ethanol, methanol and cyclohexanol;
[0048] Preferably, the oximation reaction conditions include: the molar ratio of the oxidant to cyclohexanone is 1.2 to 2.0:1, the molar ratio of the solvent to cyclohexanone is 0.5 to 5:1, the molar ratio of ammonia to cyclohexanone is 1.0 to 3.0:1, and the weight ratio of the catalyst to cyclohexanone is 0.05 to 0.2:1; the reaction temperature is 60 to 90°C, and the reaction time is 0.3 to 1.0h.
[0049] Through the above technical scheme, the present disclosure provides a titanium silicate molecular sieve and a preparation method and application thereof. In the preparation process of the titanium silicate molecular sieve, a first template having a structure shown in formula (1) and a second template having a structure shown in formula (2) are used as composite templates. The synthesized titanium silicate molecular sieve has a higher silanol content and better lipophilicity. In the catalytic oxidation reaction of organic molecules, it is beneficial to the adsorption and diffusion of organic molecules, thereby effectively improving the catalytic performance of the titanium silicate molecular sieve.
[0050] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0052] Figure 1 is the infrared hydroxyl group diagram of the molecular sieve products obtained in Example 1 and Comparative Example 1;
[0053] Figure 2 The NMR spectra of the molecular sieve products obtained in Example 1 and Comparative Example 1 are ( 29 Si NMR);
[0054] Figure 3 It is the XRD spectra of the molecular sieves obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0055] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0056] The first aspect of the present disclosure provides a method for preparing titanium silicon molecular sieve, comprising the following steps:
[0057] S1, contacting a silicon source, a titanium source, a composite template and water to obtain a raw material mixture; wherein the composite template comprises a first template and a second template; the first template is selected from one or more compounds having a structure shown in the following formula (1); the second template is selected from one or more compounds having a structure shown in the following formula (2):
[0058]
[0059] In formula (1), R1, R2, R3 and R4 are each independently selected from an alkyl group having 2 to 5 carbon atoms or an alkenyl group having 2 to 5 carbon atoms;
[0060] In formula (2), R5, R6 and R7 are each independently selected from an alkyl group having 2 to 5 carbon atoms or an alkenyl group having 2 to 5 carbon atoms; R8 is selected from an aryl group having 6 to 12 carbon atoms;
[0061] S2. subjecting the raw material mixture to a first hydrothermal crystallization treatment.
[0062] The present disclosure provides a method for preparing titanium silicate molecular sieve. In the process of preparing the titanium silicate molecular sieve, a first template having a structure shown in formula (1) and a second template having a structure shown in formula (2) are used as composite templates. The synthesized titanium silicate molecular sieve has a higher silanol content and better lipophilicity. In the catalytic oxidation reaction of organic molecules, it is beneficial to the adsorption and diffusion of organic molecules, thereby effectively improving the catalytic performance of the titanium silicate molecular sieve.
[0063] The inventors of the present invention have found through a large number of experimental studies that, compared with the conventionally used organic templates, the first template having the structure shown in the above formula (1) and the second template having the structure shown in the formula (2) are used as composite templates in the preparation process of titanium silicon molecular sieve, wherein the R8 group in the structural formula of the second template has a stronger lipophilicity, and the surface pore structure of the molecular sieve has a stronger lipophilicity after calcination, and it is easy to combine with lipophilic reactants during the reaction, thereby improving the reaction efficiency.
[0064] In the present disclosure, the number of carbon atoms of R1, R2, R3, R4, R5, R6, R7 and R8 refers to the total number of carbon atoms in the group; in R8 of the present application, aryl refers to a group containing an aromatic group (such as phenyl), and the aryl group may or may not have a substituent. When there is a substituent, the number of carbon atoms of the aryl group is the total number of carbon atoms of the aromatic group and the substituent. For example, tolyl means a methyl group connected to the phenyl group, and the number of carbon atoms of the group is 7.
[0065] In a specific embodiment, the alkyl group with 2 to 5 carbon atoms includes ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl and pentyl; the alkenyl group with 2 to 5 carbon atoms includes vinyl, propenyl, allyl, n-butenyl, isobutenyl and pentenyl.
[0066] In one embodiment, in the first template formula (1), R1, R2, R3 and R4 are each independently selected from an alkyl group having 3 carbon atoms or an alkenyl group having 3 carbon atoms.
[0067] In a specific embodiment, the alkyl group having 3 carbon atoms includes n-propyl and / or isopropyl, and the alkenyl group having 3 carbon atoms includes propenyl and / or allyl.
[0068] In a preferred embodiment, the first template is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, butyltripropylammonium hydroxide, 1-butenyltripropylammonium hydroxide, 2-butenyltripropylammonium hydroxide and 3-butenyltripropylammonium hydroxide; preferably selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, butyltripropylammonium hydroxide and 1-butenyltripropylammonium hydroxide.
[0069] In one embodiment, in the second template formula (2), R5, R6 and R7 are each independently selected from an alkyl group having 2 to 4 carbon atoms or an alkenyl group having 2 to 4 carbon atoms; and R8 is selected from an aryl group having 6 to 8 carbon atoms.
[0070] In a specific embodiment, the alkyl group having 2 to 4 carbon atoms is selected from one or more of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl; the alkenyl group having 2 to 4 carbon atoms is selected from one or more of vinyl, propenyl, allyl, n-butenyl and isobutenyl; the aryl group having 6 to 8 carbon atoms is selected from one or more of phenyl, tolyl, benzyl (benzyl), ethylphenyl, phenethyl, p-tolyl, m-tolyl, o-tolyl, propylphenyl, n-butylphenyl, isobutylphenyl, o-ethylphenyl, p-ethylphenyl and m-ethylphenyl.
[0071] In one embodiment, the second template is selected from one or more of phenyltripropylammonium hydroxide, p-tolyltripropylammonium hydroxide, p-ethylphenyltripropylammonium hydroxide, benzyltripropylammonium hydroxide, phenethyltripropylammonium hydroxide, phenylallyldipropylphenylammonium hydroxide, p-tolylallyldipropylammonium hydroxide, p-ethylphenylallyldipropylammonium hydroxide, benzylallyldipropylammonium hydroxide, phenethylallyldipropylammonium hydroxide, phenylpropylenedipropylammonium hydroxide, p-tolylpropylenedipropylammonium hydroxide, p-ethylphenylpropylenedipropylammonium hydroxide, benzylpropylenedipropylammonium hydroxide and phenethylpropylenedipropylammonium hydroxide; preferably, it is selected from one or more of phenyltripropylammonium hydroxide, p-tolyltripropylammonium hydroxide, phenylallyldipropylphenylammonium hydroxide, benzylallyldipropylammonium hydroxide and phenylpropylenedipropylammonium hydroxide.
[0072] In one embodiment, the silicon source is selected from at least one of organic silicone grease, solid silica gel, white carbon black and silica sol; preferably, it is selected from at least one of organic silicone grease, solid silica gel and white carbon black. Preferably, the SiO2 content in the solid silicon source (solid silica gel, white carbon black and silica sol) is not less than 99.99% by weight based on dry weight, and the total mass content of Fe, Al and Na impurities is less than 10ppm; for example, the SiO2 content is 99.99-100% by weight, usually greater than 99.99 and less than 100% by weight. The solid silicon source can be high-purity silica gel and / or white carbon black, preferably white carbon black; wherein the SiO2 content in the high-purity silica gel is preferably greater than or equal to 99.99% by weight, for example, greater than 99.99% by weight and less than 100% by weight, and the total mass content of Fe, Al and Na impurities is less than 10ppm. Based on the dry weight of the white carbon black, the SiO2 content in the white carbon black is preferably greater than or equal to 99.99 weight %, for example, 99.99 to 100 weight %, for example, greater than 99.99 weight % and less than 100 weight %, and the total mass content of Fe, Al and Na impurities in the white carbon black is less than 10 ppm in terms of atoms. The specific surface area of the white carbon black is between 20 and 1000 m 2 / g, preferably 50 to 400 m 2 / g.
[0073] In a preferred embodiment, the organic silicone grease is selected from one or more compounds having the structure shown in the following formula (A):
[0074]
[0075] R a , R b , R c and R d Each is independently selected from an alkyl group having 1 to 4 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, the R a , R b , R c and R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl; further preferably, the organic silicone grease is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicate; further preferably, it is selected from one or more of tetramethyl silicate, tetraethyl silicate and dimethyl diethyl silicate.
[0076] In one embodiment, the titanium source is selected from one or more of an organic titanium source and an inorganic titanium source;
[0077] Preferably, the organic titanium source is a titanium-containing organic acid ester, selected from at least one of the structures represented by the following formula (B):
[0078]
[0079] Where R e , R f , R g and R h are each selected from an alkyl group having 1 to 6 carbon atoms, preferably a straight-chain alkyl group having 1 to 4 carbon atoms and a branched-chain alkyl group having 3 to 6 carbon atoms, and more preferably R e , R f , R g and R h are independently selected from a straight chain alkyl group having 2 to 4 carbon atoms and a branched chain alkyl group having 2 to 4 carbon atoms; optionally, R e , R f , R g and R h Each of the following groups is independently selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl and isohexyl; preferably each of the following groups is independently selected from one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl;
[0080] Preferably, the inorganic titanium source is selected from one or more of chloride, nitrate or sulfate of titanium;
[0081] Further preferably, the titanium source is selected from one or more of titanium tetrachloride, titanium sulfate, titanium nitrate, tetraethyl titanate, tetrapropyl titanate and tetrabutyl titanate.
[0082] In the present disclosure, the silicon source, the titanium source, the first template and the second template can be purchased through common commercial channels, or prepared by known methods.
[0083] In one embodiment, in step S1, the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): composite template: water is 1: (0.001-0.040): (0.05-0.30): (5-40); preferably 1: (0.010-0.035): (0.10-0.20): (10-30). The titanium silicalite molecular sieve is prepared according to the optimized raw material molar ratio in this embodiment, which can further improve the lipophilicity and catalytic performance of the titanium silicalite molecular sieve.
[0084] In a preferred embodiment, in the composite template, the molar ratio of the first template to the second template is 1:(0.01-0.10), preferably 1:(0.02-0.08), and more preferably 1:(0.03-0.08). According to this embodiment, controlling the molar ratio of the first template to the second template is beneficial to improving the lipophilicity and catalytic performance of the titanium silicalite.
[0085] In a specific embodiment, step S1 further comprises the step of hydrolyzing and removing alcohol from the raw material mixture;
[0086] Optionally, the conditions for the hydrolysis and alcohol removal treatment include: treating at 5-120° C. for 0.5-48 h; preferably treating at 50-100° C. for 1-24 h, and more preferably treating at 60-90° C. for 5-20 h.
[0087] In one embodiment, in step S2, the conditions of the first hydrothermal crystallization treatment include: a hydrothermal crystallization temperature of 150 to 200°C, a hydrothermal crystallization time of 2 to 168 hours, and a hydrothermal crystallization pressure of autogenous pressure; preferably, a hydrothermal crystallization temperature of 160 to 190°C, and a hydrothermal crystallization time of 4 to 80 hours; further preferably, a hydrothermal crystallization temperature of 165 to 188°C, and a hydrothermal crystallization time of 5 to 40 hours. The optimized hydrothermal crystallization treatment conditions in this embodiment can further improve the lipophilicity and catalytic performance of the molecular sieve.
[0088] In a specific embodiment, after step S2, it also includes: separating the first hydrothermal crystallization product to obtain a solid product; the separation includes one or more of centrifugation, filtration, evaporation, sedimentation, and membrane separation, and the separation can be performed according to conventional operations and conditions in the art. Among them, it also includes returning the liquid product after separating the solid product to the first step for preparing silica-titanium colloid. The liquid product includes titanium silicon molecular sieve nanocrystals, amorphous silicon, amorphous titanium and template. The specific liquid recycling process is a conventional operation of those skilled in the art.
[0089] In one embodiment, the method further comprises: drying and / or calcining the crystallized product obtained by the first hydrothermal crystallization treatment to obtain a solid product. The drying treatment can remove most of the water in the molecular sieve to reduce the amount of water evaporation in the solid during calcination; the purpose of calcination is to remove the template in the molecular sieve.
[0090] In one embodiment, the drying conditions include: a drying temperature of 100 to 200° C. and a drying time of 2 to 10 hours;
[0091] The conditions for the calcination treatment include: a calcination temperature of 350-650° C. and a calcination time of 2-10 hours; preferably, a calcination temperature of 450-550° C. and a calcination time of 3-8 hours.
[0092] In one embodiment, the method further comprises: contacting the solid product with an acid solution for acid treatment, and then adding a pH regulator for neutralization treatment to obtain an intermediate product. The acid solution treatment is conducive to removing the amorphous structure in the molecular sieve pores.
[0093] In one embodiment, in the acid treatment, the acid is selected from one or more of hydrochloric acid, nitric acid, phosphoric acid, carbonic acid, sulfuric acid and acetic acid; the acid concentration is 0.1-1.0 mol / L, and the mass volume ratio of the acid to the solid product is 80-150 g solid product / 1 L acid; optionally, the conditions of the acid treatment include: a contact temperature of 50-150° C., preferably 60-100° C., and a contact time of 0.5-5.0 h, preferably 1.0-3.5 h;
[0094] Optionally, the pH adjuster is selected from one or more alkali solutions; the alkali solution is selected from one or more of ammonia water, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, and sodium bicarbonate, and the neutralization treatment adjusts the pH value of the solution to 5-7.
[0095] In one embodiment, the method further comprises: mixing the intermediate product with a third template and performing a second hydrothermal crystallization treatment. By performing the second hydrothermal crystallization treatment on the intermediate product after the acid treatment, a multi-level pore structure can be prepared inside the molecular sieve to improve the diffusion performance.
[0096] In a specific embodiment, the mass ratio of the intermediate product to the third template is 2 to 20:1; preferably 5 to 15:1;
[0097] The conditions of the second hydrothermal crystallization treatment include: a hydrothermal crystallization temperature of 150 to 200° C., a hydrothermal crystallization time of 10 to 40 hours, and a hydrothermal crystallization pressure of autogenous pressure; preferably, the hydrothermal crystallization temperature is 160 to 180° C., and the hydrothermal crystallization time is 20 to 30 hours;
[0098] Optionally, the third template is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, allyltripropylammonium hydroxide and butyltripropylammonium hydroxide.
[0099] The second aspect of the present disclosure provides a titanium silicon molecular sieve prepared according to the method described in the first aspect of the present disclosure.
[0100] The third aspect of the present disclosure provides a titanium silicon molecular sieve having the following infrared hydroxyl spectrum characteristics:
[0101] The infrared hydroxyl spectrum of the titanium silicalite molecular sieve is 3200-3800 cm -1 The peak area calculated by normalizing the characteristic peak within the wave number range is recorded as I1, and I1 is any value between 1.35 and 6.55, preferably any value between 1.35 and 5.38, and more preferably any value between 3.03 and 5.05. The total amount of hydroxyl groups in the titanium silicon molecular sieve provided by the present disclosure is reduced; and compared with the titanium silicon molecular sieve prepared by the traditional synthesis process, in the infrared hydroxyl spectrum of the titanium silicon molecular sieve, 3740cm -1 and 3500cm -1 The intensity of the characteristic peak at the position is weakened. -1 The characteristic peak at the wavenumber position indicates the terminal hydroxyl group, which is 3500±10cm -1 The characteristic peak at the wave number position represents the nested hydroxyl group. The titanium silicon molecular sieve provided by the present disclosure has fewer nested hydroxyl groups and terminal hydroxyl groups, and the total number of hydroxyl groups after normalization is 20% to 80% of the titanium silicon molecular sieve synthesized by general crystallization. The normalization refers to the infrared hydroxyl spectrum obtained by measurement, after deducting the baseline, integrating the peak area and dividing it by the sample mass to obtain the infrared hydroxyl peak area value of the unit mass sample.
[0102] In one specific embodiment, the infrared hydroxyl spectrum of the titanium silicon molecular sieve (such as comparative example 1 of the present disclosure) prepared by a conventional synthesis process is 3200-3800 cm -1 The peak area of the characteristic peak within the wavenumber range is recorded as I2;
[0103] I0 defined by the following formula (S-1) is any value between 20% and 80%;
[0104] I0=I1 / I2 formula (S-1);
[0105] Preferably, I0 is any value between 45% and 75%.
[0106] In a preferred embodiment, the titanium silicalite molecular sieve has the following nuclear magnetic resonance silicon spectrum characteristics: the intensity at the chemical shift of -103±1ppm in the nuclear magnetic resonance silicon spectrum of the titanium silicalite molecular sieve is recorded as Q3, and the intensity at the chemical shift of -113±1ppm in the nuclear magnetic resonance silicon spectrum of the titanium silicalite molecular sieve is recorded as Q3', and Q0 defined by the following formula (S-2) is any value between 0.01 and 0.07;
[0107] Q0=Q3 / Q3' formula (S-2).
[0108] In a preferred embodiment, Q0 is any value between 0.02 and 0.06.
[0109] In a specific embodiment, the intensity at the chemical shift of -103±1ppm in the nuclear magnetic resonance silicon spectrum of the titanium silicate molecular sieve prepared by the traditional synthesis process is recorded as Q3", and the Q3 / Q3"×100% of the titanium silicate molecular sieve provided by the present disclosure is 60-80%, indicating that the titanium silicate molecular sieve provided by the present disclosure has fewer Q3 species than the titanium silicate molecular sieve synthesized by the traditional method, indicating that the molecular sieve has fewer hydroxyl groups and is more lipophilic.
[0110] In a specific embodiment, the titanium silicon molecular sieve prepared by a conventional synthesis process can be prepared by a preparation method comprising the following steps:
[0111] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): template: water of 1: 0.01-0.10: 0.10-0.50: 15-20, the traditional template tetrapropylammonium hydroxide (25 wt%) solution, silicon source (TEOS), titanium source and deionized water are stirred at 50-90°C for about 2-20 hours to obtain a sol. Then crystallize at 150-200°C for 50-100 hours, filter the solid obtained by centrifugation, wash with distilled water, dry at 90-130°C for 3-10 hours, and roast at 500-600°C for 2-10 hours; then mix with hydrochloric acid solution, and add appropriate amount of ammonia water to neutralize after hydrochloric acid treatment. Then mix it with tetrapropylammonium hydroxide aqueous solution and hydrothermally treat it at 160-180°C for 20-40 hours to obtain a traditional molecular sieve solid. The selection range of the traditional template is the same as that of the first template in the preparation method provided in the present invention, which will not be repeated here; the selection range of the silicon source and the titanium source is the same as that of the silicon source and the titanium source in the preparation method provided in the present invention, which will not be repeated here.
[0112] In one embodiment, the molar ratio of silicon atoms to titanium atoms in the titanium silicon molecular sieve is 10 to 100:1, preferably 20 to 50:1.
[0113] In a specific embodiment, the average particle size of the molecular sieve particles of the titanium silicon molecular sieve is 0.10 to 0.50 μm, preferably 0.20 to 0.40 μm; the BET specific surface area is 400 to 500 m 2 / g, preferably 430 to 470 m 2 / g; micropore specific surface area is 350~450m 2 / g, preferably 380 to 410 m 2 / g; total pore volume is 0.20~0.50cm 3 / g, preferably 0.30 to 0.40 cm 3 / g; mesopore volume is 0.03~0.30cm 3 / g, preferably 0.15 to 0.25 cm 3 / g.
[0114] In a specific embodiment, the molecular sieve can have an AEL, AFI, AFN, BEC, CFI, CHA, CON, EUO, FAU, FER, IMF, LTA, MER, MFI, MEL, MOR, MWW, RHO, TON, *BEA, *EWT or a two-dimensional hexagonal phase structure; preferably, it has an MFI structure.
[0115] Specifically, the titanium silicon molecular sieve provided by the present disclosure can be used as a catalytically active component, and its unique skeleton elements can be used, or it can be used as a carrier to further load active centers, or it can be prepared into a catalyst by mechanical mixing, kneading, tableting, extrusion, spraying, rolling ball, oil column, etc. with other catalysts, co-catalysts, structural additives, electronic additives, binders, inert carriers, etc. The reagents and preparation processes used can all be conventional reagents or processes in the art.
[0116] The fifth aspect of the present disclosure provides the use of the titanium silicon molecular sieve described in the second aspect or the third aspect of the present disclosure in the catalytic reaction of organic matter and / or the adsorption separation process.
[0117] In the present disclosure, the organic matter reaction includes: catalytic oxidation reaction (olefin oxidation / epoxidation to prepare aldehydes, ketones, acids, epoxy compounds, vicinal diols; alkane oxidation to prepare alcohols, aldehydes, acids; alcohol oxidation to prepare ketones, acids; aldehyde oxidation to prepare acids; aromatic oxidation to prepare phenols; sulfide oxidation to prepare sulfoxides and sulfones), reduction reaction, oximation reaction (aldehyde / ketone ammoximation to prepare amides and lactams), aldol condensation reaction, substitution / halogenation reaction, elimination reaction, transesterification reaction, dehydration reaction, etherification reaction, esterification reaction, double bond / triple bond addition reaction, diene addition reaction, Beckmann rearrangement reaction (cyclohexanone oxime gas phase rearrangement to prepare caprolactam), hydrogen transfer reaction, etc. The adsorption separation process includes: adsorption separation of hydrocarbons (such as ethane ethylene, butene dibutylene), gas (such as helium separation), inorganic matter (such as cesium ion separation) and other substances.
[0118] In a specific embodiment, the organic catalytic reaction includes olefin epoxidation to prepare epoxy compounds, olefin chlorohydrinization to prepare chlorohydrin, aldehyde / ketone ammoximation to prepare aldehyde / ketone oxime and ketone Beckmann rearrangement to prepare amide.
[0119] In a specific embodiment, the organic catalytic reaction is cyclohexanone ammoximation, optionally comprising the following steps:
[0120] Under oximation reaction conditions, cyclohexanone, an oxidant, ammonia and a catalyst are contacted to carry out an oxidation reaction; the catalyst comprises the titanium silicon molecular sieve;
[0121] Optionally, the oxidant is selected from one or more of hydrogen peroxide, tert-butyl hydroperoxide, cumene hydroperoxide and m-chloroperbenzoic acid; preferably, the reaction is carried out in the presence of a solvent; the solvent is selected from one or more of n-butanol, tert-butanol, ethanol, methanol and cyclohexanol;
[0122] Preferably, the oximation reaction conditions include: the molar ratio of the oxidant to cyclohexanone is 1.2 to 2.0:1, the molar ratio of the solvent to cyclohexanone is 0.5 to 5:1, the molar ratio of ammonia to cyclohexanone is 1.0 to 3.0:1, and the weight ratio of the catalyst to cyclohexanone is 0.05 to 0.2:1; the reaction temperature is 60 to 90°C, and the reaction time is 0.3 to 1.0h.
[0123] In the application of the titanium silicalite provided in the present disclosure, the titanium silicalite or the catalyst containing the titanium silicalite can be used in the form of powder or shaped spheres, strips, cakes, granules, etc., and can be mixed with other catalysts; the application can be carried out in various reactors such as kettle reactors, slurry bed reactors, fixed bed reactors, fluidized bed reactors, moving bed reactors, microchannel reactors, etc.; the reaction raw materials and catalysts can be fed all at once, intermittently, or continuously.
[0124] It will be understood by those skilled in the art that the separation of the product and the catalyst can be achieved in a variety of ways. For example, when the original powdered molecular sieve is used as the catalyst, the product separation and the catalyst recovery and reuse can be achieved by sedimentation, filtration, centrifugation, evaporation, membrane separation, etc. Alternatively, the catalyst can be formed and loaded into a fixed bed reactor, and the catalyst can be recovered after the reaction is completed. The separation and recovery methods of various catalysts can be known methods.
[0125] The present disclosure is further described in detail by way of examples. The raw materials used in the examples can all be obtained through commercial sources.
[0126] The structure of the molecular sieve was determined by XRD analysis, and the test instrument was Siemens D5005 X-ray diffractometer; the test method included: Cu target, Kα radiation, Ni filter, tube point voltage 40kV, tube current 250mA, scintillation counter, step width 0.02°. Scanning range 2θ = 5° to 35°, scanning rate 0.4 (°) / min.
[0127] The testing instrument for the infrared hydroxyl spectrum of molecular sieves is a Nicolet 8210 Fourier transform infrared spectrometer; the testing method includes pressing the sample into a self-supporting sheet, placing it in an infrared cell, and treating the sample at 450°C for 3 hours under 1×10-3Pa conditions.
[0128] The testing instrument for molecular sieve nuclear magnetic silicon spectrum is BrukerAVANCEIII 600WB nuclear magnetic resonance spectrometer; the testing method includes resonance spectrum 59.588MHz, magic angle speed 3kHz, pulse width 1.5μs (corresponding to 20° bevel angle), cycle delay time 3s, and scanning times 3000 times.
[0129] The content of the template in the molecular sieve is measured by thermogravimetric method, and the weight loss from the weight loss curve above 200°C until the weight loss curve stabilizes is calculated as the template content of the molecular sieve.
[0130] The chemical composition of the molecular sieves was determined by XRF analysis.
[0131] The specific surface area of the molecular sieve is measured by nitrogen low temperature adsorption desorption method, and the micropore specific surface area is calculated by BET method; the pore volume and pore distribution are determined according to the method described in RIPP 151-90 in "Petrochemical Analysis Methods" compiled by Yang Cuiding et al. (Science Press, first edition, published in September 1990).
[0132] Unless otherwise specified, the raw materials used in the examples and comparative examples were all analytically pure reagents.
[0133] Example 1
[0134] This example illustrates the preparation of TS-1-A without a template using the method disclosed herein.
[0135] According to the molar ratio of silicon source (calculated as SiO2): titanium source (calculated as TiO2): composite template (total molar number of two templates): water of 1:0.03:0.20:20, tetrapropylammonium hydroxide (25 weight%) solution and phenyltripropylammonium hydroxide (30 weight%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water are stirred at 80°C for about 8 hours to obtain a sol, in which the molar ratio of tetrapropylammonium hydroxide (first template) to phenyltripropylammonium hydroxide (second template) is 1:0.05. Then crystallize at 167°C for 34h (first hydrothermal crystallization treatment); then filter the solid obtained by centrifugation, wash with distilled water, dry at 100°C for 3 hours, and roast at 550°C for 6h; then mix with 0.2mol / L hydrochloric acid solution for acid treatment, the conditions of acid treatment include: the mass volume ratio of acid to the solid product is 100g solid product / 1L acid, the contact temperature is 75°C, the contact time is 2h, and after hydrochloric acid treatment, add appropriate amount of ammonia water to neutralize to pH value of about 6.5. Then, mix the intermediate product obtained after acid treatment with an aqueous solution of tetrapropylammonium hydroxide (third template, 25 weight%), the mass ratio of the intermediate product to the third template (effective mass of the template) is 10, and hydrothermally treat at 173°C for 17h (second hydrothermal crystallization treatment) to obtain a molecular sieve solid, recorded as TS-1-A.
[0136] The XRD spectra of titanium silicalite TS-1-A and titanium silicalite D-1 prepared in Comparative Example 1 (using the traditional method) are as follows: Figure 3 As shown by Figure 3It can be seen that the titanium silicate molecular sieve TS-1-A prepared in this example has a similar XRD curve to the titanium silicate molecular sieve D-1 obtained in Comparative Example 1, indicating that the titanium silicate molecular sieve prepared in this example has an MFI structure.
[0137] Example 2
[0138] This example illustrates the preparation of TS-1-B without a template using the method disclosed herein.
[0139] According to the molar ratio of silicon source (calculated as SiO2): titanium source (calculated as TiO2): composite template (total molar number of two templates): water of 1:0.03:0.20:20, butyltripropylammonium hydroxide (25 weight%) solution and phenylallyldipropylammonium hydroxide (20 weight%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water were stirred at 69°C for about 12 hours to obtain a sol, in which the molar ratio of butyltripropylammonium hydroxide (first template) to phenylallyldipropylammonium hydroxide (second template) was 1:0.07. Then crystallize at 168°C for 29h, filter the solid obtained by centrifugation, wash with distilled water, dry at 100°C for 3 hours, and roast at 550°C for 6h; then mix with 0.5mol / L hydrochloric acid solution, the acid treatment conditions include: the mass volume ratio of acid to the solid product is 120g solid product / 1L acid, the contact temperature is 78°C, the contact time is 3h, and after hydrochloric acid treatment, add appropriate amount of ammonia water to neutralize to pH value of about 5.5. Then, mix the intermediate product obtained after acid treatment with tetrapropylammonium hydroxide (third template, 25 weight%) aqueous solution, the mass ratio of the intermediate product to the third template (effective mass of the template) is 6, and hydrothermally treat at 167°C for 25h (second hydrothermal crystallization treatment) to obtain a molecular sieve solid, recorded as TS-1-B.
[0140] Example 3
[0141] This example illustrates the preparation of TS-1-C without a template using the method disclosed herein.
[0142] According to the molar ratio of silicon source (calculated as SiO2): titanium source (calculated as TiO2): composite template (total molar number of two templates): water of 1:0.03:0.15:20, tetrabutylammonium hydroxide (25 weight %) solution and benzyltripropylammonium hydroxide (22 weight %) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water were stirred at 87°C for about 16 hours to obtain a sol, in which the molar ratio of tetrabutylammonium hydroxide (first template) to benzyltripropylammonium hydroxide (second template) was 1:0.03. Then, crystallization was carried out at 168°C for 29h, and then the solid obtained by centrifugation was filtered, washed with distilled water, dried at 100°C for 3 hours, and roasted at 550°C for 6h; then mixed with 1.0mol / L hydrochloric acid solution, and the conditions of acid treatment included: the mass volume ratio of acid to the solid product was 150g solid product / 1L acid, the contact temperature was 100°C, the contact time was 1.0h, and after hydrochloric acid treatment, an appropriate amount of ammonia water was added to neutralize to a pH value of about 7. Then, the intermediate product obtained after the acid treatment was mixed with a tetrapropylammonium hydroxide (third template, 25 weight%) aqueous solution, the mass ratio of the intermediate product to the third template (effective mass of the template) was 15, and hydrothermally treated at 168°C for 32h (second hydrothermal crystallization treatment) to obtain a molecular sieve solid, recorded as TS-1-C.
[0143] Example 4
[0144] This example illustrates the preparation of TS-1-D without a template using the method disclosed herein.
[0145] According to the molar ratio of silicon source (calculated as SiO2): titanium source (calculated as TiO2): composite template (total molar number of two templates): water of 1:0.03:0.15:20, tetrapropylammonium hydroxide (25 weight%) solution and benzylpropylenedipropylammonium hydroxide (22 weight%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water were stirred at 89°C for about 17 hours to obtain a sol, in which the molar ratio of tetrabutylammonium hydroxide (first template) to benzyltripropylammonium hydroxide (second template) was 1:0.06. Then crystallize at 183°C for 23h, then filter the solid obtained by centrifugation, wash with distilled water, dry at 100°C for 3 hours, and roast at 550°C for 6h; then mix with 0.1mol / L hydrochloric acid solution, the acid treatment conditions include: the mass volume ratio of acid to the solid product is 80g solid product / 1L acid, the contact temperature is 60°C, the contact time is 3.5h, and after hydrochloric acid treatment, add appropriate amount of ammonia water to neutralize to pH value of about 6.8. Then, the intermediate product obtained after acid treatment is mixed with an aqueous solution of tetrapropylammonium hydroxide (third template, 25 weight%), the mass ratio of the intermediate product to the third template (effective mass of the template) is 5, and hydrothermally treated at 172°C for 17h (second hydrothermal crystallization treatment) to obtain a molecular sieve solid, recorded as TS-1-D.
[0146] Example 5
[0147] This example illustrates the preparation of TS-1-E without a template using the disclosed method.
[0148] According to the molar ratio of silicon source (calculated as SiO2): titanium source (calculated as TiO2): composite template (total molar number of two templates): water of 1:0.03:0.15:20, a solution of propylene tripropyl ammonium hydroxide (25 weight%) and a solution of phenethyl tripropyl ammonium hydroxide (26 weight%), tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water were stirred at 75°C for about 8 hours to obtain a sol, in which the molar ratio of propylene tripropyl ammonium hydroxide (first template) to phenethyl tripropyl ammonium hydroxide (second template) was 1:0.08. Then, crystallization was carried out at 190°C for 16 hours, and then the solid obtained by centrifugation was filtered, washed with distilled water, dried at 100°C for 3 hours, and roasted at 550°C for 6 hours; then mixed with 0.7mol / L hydrochloric acid solution, and the conditions of acid treatment included: the mass volume ratio of acid to the solid product was 140g solid product / 1L acid, the contact temperature was 65°C, the contact time was 2.5h, and after hydrochloric acid treatment, an appropriate amount of ammonia water was added to neutralize to a pH value of about 7. Then, the intermediate product obtained after the acid treatment was mixed with an aqueous solution of tetrapropylammonium hydroxide (the third template, 25 weight%), the mass ratio of the intermediate product to the third template (the effective mass of the template) was 13, and hydrothermally treated at 166°C for 24h (the second hydrothermal crystallization treatment) to obtain a molecular sieve solid, which was recorded as TS-1-E.
[0149] Example 6
[0150] This example illustrates the preparation of TS-1-F without a template using the method disclosed herein.
[0151] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): composite template (total molar number of two templates): water of 1:0.03:0.20:20, tetrapropylammonium hydroxide (25 wt%) solution and phenyltripropylammonium hydroxide (30 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water were stirred at 72°C for about 17 hours to obtain a sol, wherein the molar ratio of tetrapropylammonium hydroxide (first template) to phenyltripropylammonium hydroxide (second template) was 1:0.04. Then, crystallization was carried out at 173°C for 12 hours, and then the solid obtained by centrifugation was filtered, washed with distilled water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a molecular sieve solid, which was recorded as TS-1-F.
[0152] Example 7
[0153] This example illustrates the preparation of TS-1-G without a template using the disclosed method.
[0154] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): composite template (total molar number of two templates): water of 1:0.03:0.20:20, butyl tripropyl ammonium hydroxide (25 wt%) solution and phenyl allyl dipropyl ammonium hydroxide (20 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water were stirred at 83°C for about 8 hours to obtain a sol, wherein the molar ratio of butyl tripropyl ammonium hydroxide (first template) to phenyl allyl dipropyl ammonium hydroxide (second template) was 1:0.03. Then, crystallization was carried out at 168°C for 24 hours, and then the solid obtained by centrifugation was filtered, washed with distilled water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a molecular sieve solid, which was recorded as TS-1-G.
[0155] Example 8
[0156] This example illustrates the preparation of TS-1-H without a template using the disclosed method.
[0157] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): composite template (total molar number of two templates): water of 1:0.03:0.15:20, tetrabutylammonium hydroxide (25 wt%) solution and benzyltripropylammonium hydroxide (22 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water were stirred at 95°C for about 22 hours to obtain a sol, wherein the molar ratio of tetrabutylammonium hydroxide (first template) to benzyltripropylammonium hydroxide (second template) was 1:0.07. Then, crystallization was carried out at 183°C for 15 hours, and then the solid obtained by centrifugation was filtered, washed with distilled water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a molecular sieve solid, which was recorded as TS-1-H.
[0158] Example 9
[0159] This example illustrates the preparation of TS-1-I without a template using the disclosed method.
[0160] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): composite template (total molar number of two templates): water of 1:0.03:0.15:20, tetrapropylammonium hydroxide (25 wt%) solution and benzylpropenyldipropylammonium hydroxide (22 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water were stirred at 55°C for about 24 hours to obtain a sol, wherein the molar ratio of tetrapropylammonium hydroxide (first template) to benzylpropenyldipropylammonium hydroxide (second template) was 1:0.08. Then, crystallization was carried out at 155°C for 13 hours, and then the solid obtained by centrifugation was filtered, washed with distilled water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a molecular sieve solid, which was recorded as TS-1-I.
[0161] Example 10
[0162] This example illustrates the preparation of TS-1-J without a template using the disclosed method.
[0163] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): composite template (total molar number of two templates): water of 1:0.03:0.15:20, a 25 wt% solution of propenyl tripropyl ammonium hydroxide and a 26 wt% solution of phenethyl tripropyl ammonium hydroxide, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water were stirred at 93°C for about 1 hour to obtain a sol, wherein the molar ratio of propenyl tripropyl ammonium hydroxide (first template) to phenethyl tripropyl ammonium hydroxide (second template) was 1:0.08. Then, crystallization was carried out at 195°C for 30 hours, and then the solid obtained by centrifugation was filtered, washed with distilled water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a molecular sieve solid, which was recorded as TS-1-J.
[0164] Embodiment 11
[0165] This example uses a method similar to that of Example 1 to prepare titanium silicon molecular sieve TS-1-K, which is different from Example 1 in that the silicon source is replaced by tetramethyl silicate, the titanium source is replaced by titanium tetrachloride, the acid solution is replaced by nitric acid, and the third template is replaced by allyl tripropylammonium hydroxide, and the rest of the process is the same as that of Example 1. A molecular sieve solid is obtained, which is recorded as TS-1-K.
[0166] Example 12
[0167] This example uses a method similar to that of Example 1 to prepare titanium silicalite molecular sieve TS-1-L, except that the second template is replaced with phenyltripropylammonium hydroxide, and the rest of the process is the same as that of Example 1. A molecular sieve solid is obtained, which is recorded as TS-1-L.
[0168] Example 13
[0169] This example uses a method similar to that of Example 1 to prepare titanium silicon molecular sieve TS-1-M, except that:
[0170] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): composite template (total molar number of two templates): water of 1:0.004:0.08:8, tetrapropylammonium hydroxide (25 wt%) solution and phenyltripropylammonium hydroxide (30 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water were stirred at 80°C for about 8 hours to obtain a sol; wherein the molar ratio of tetrapropylammonium hydroxide (first template) to phenyltripropylammonium hydroxide (second template) was 1:0.1. The rest of the process was the same as in Example 1 to obtain a molecular sieve solid, recorded as TS-1-M.
[0171] Embodiment 14
[0172] This example uses a method similar to that of Example 1 to prepare titanium silicon molecular sieve TS-1-M, except that:
[0173] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): composite template (total molar number of two templates): water of 1:0.1:0.4:50, tetrapropylammonium hydroxide (25 wt%) solution and phenyltripropylammonium hydroxide (30 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water were stirred at 80°C for about 8 hours to obtain a sol;
[0174] The molar ratio of tetrapropylammonium hydroxide (the first template agent) to phenyltripropylammonium hydroxide (the second template agent) is 1:0.5. The remaining process is the same as that of Example 1 to obtain a molecular sieve solid, which is recorded as TS-1-N.
[0175] Embodiment 15
[0176] According to the molar ratio of silicon source (calculated as SiO2): titanium source (calculated as TiO2): composite template (total molar number of two templates): water of 1:0.03:0.20:20, tetrapropylammonium hydroxide (25 weight%) solution and phenyltripropylammonium hydroxide (30 weight%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water are stirred at 80°C for about 8 hours to obtain a sol, in which the molar ratio of tetrapropylammonium hydroxide (first template) to phenyltripropylammonium hydroxide (second template) is 1:0.05. Then crystallize at 150°C for 3h (first hydrothermal crystallization treatment); then filter the solid obtained by centrifugation, wash with distilled water, dry at 100°C for 3 hours, and roast at 350°C for 10h; then mix with 0.2mol / L hydrochloric acid solution for acid treatment, the conditions of acid treatment include: the mass volume ratio of acid to the solid product is 100g solid product / 1L acid, the contact temperature is 50°C, the contact time is 0.5h, and after hydrochloric acid treatment, add appropriate amount of ammonia water to neutralize to pH value of about 6.5. Then, mix the intermediate product obtained after acid treatment with an aqueous solution of tetrapropylammonium hydroxide (third template, 25 weight%), the mass ratio of the intermediate product to the third template (effective mass of the template) is 2, and hydrothermally treat at 150°C for 10h (second hydrothermal crystallization treatment) to obtain a molecular sieve solid, recorded as TS-1-O.
[0177] Comparative Example 1
[0178] In this comparative example, no second template is added during the preparation of the titanium silicate molecular sieve, that is, the titanium silicate molecular sieve is prepared by a traditional method.
[0179] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): template: water of 1:0.03:0.15:20, tetrapropylammonium hydroxide (25 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water were stirred at 78°C for about 10 hours to obtain a sol. Then crystallization was carried out at 178°C for 20 hours, and then the solid obtained by centrifugation was filtered, washed with distilled water, dried at 100°C for 3 hours, and roasted at 550°C for 6 hours; then mixed with hydrochloric acid solution, and neutralized with appropriate amount of ammonia water after hydrochloric acid treatment. Then it was mixed with tetrapropylammonium hydroxide aqueous solution and hydrothermally treated at 166°C for 24 hours to obtain a molecular sieve solid, which was recorded as D-1.
[0180] Comparative Example 2
[0181] In this comparative example, no second template is added during the preparation of the titanium silicalite molecular sieve, and no acid treatment and second hydrothermal crystallization treatment are performed.
[0182] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): template: water of 1:0.03:0.20:20, tetrapropylammonium hydroxide (25 wt%) solution, tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4] and deionized water were stirred at 69°C for about 18 hours to obtain a sol. Then, crystallization was carried out at 172°C for 10 hours, and then the solid obtained by centrifugation was filtered, washed with distilled water, dried at 100°C for 3 hours, and calcined at 550°C for 6 hours to obtain a molecular sieve solid, which was recorded as D-2.
[0183] The infrared hydroxyl spectrum characteristic data and nuclear magnetic silicon spectrum characteristic data of the molecular sieve products obtained in the above examples and comparative examples are listed in the following Table 1, and the structural parameters and other data of the molecular sieve products are listed in the following Table 2.
[0184] Wherein, I0=(the total hydroxyl area of infrared hydroxyl spectrum of titanium silicon molecular sieve of Example 1 I1 / the total hydroxyl area of infrared hydroxyl spectrum of titanium silicon molecular sieve of Comparative Example 1 I2)×100%; wherein the total hydroxyl area of infrared hydroxyl spectrum refers to 3200~3800cm -1 The sum of the normalized peak areas of the characteristic peaks within the range.
[0185] Q0 = (Q in the nuclear magnetic silicon spectrum of the titanium silicon molecular sieve in the embodiment 3 Peak area Q3 at the position of species spectrum peak (-103ppm) / Q in the nuclear magnetic silicon spectrum of comparative example 1 titanium silicon molecular sieve 3 The peak area at the position of the species spectrum peak (-103ppm) is (23')×100%.
[0186] Table 1
[0187]
[0188] According to the data in Table 1 above, compared with Comparative Examples 1 and 2, the infrared hydroxyl spectrum of the titanium silicon molecular sieve prepared by the method provided by the present disclosure shows fewer nested hydroxyl groups and terminal hydroxyl groups. The infrared hydroxyl spectrum of the titanium silicon molecular sieve prepared by the traditional synthesis method in Comparative Example 1 shows that the number of hydroxyl groups at 3200-3800 cm -1 Characteristic peaks in the range (including 3740cm -1 and 3500cm -1 The normalized peak area sum I2 of the characteristic peak at the position is used as a comparison benchmark. The infrared hydroxyl spectrum of the titanium silicon molecular sieve prepared in the embodiment of the present disclosure has a peak area of 3200-3800 cm -1 Characteristic peaks in the range (including 3740cm -1 and 3500cm -1The normalized peak area sum I1 of the characteristic peak at the position is 60-80% of that of the titanium silicon molecular sieve obtained by the traditional synthesis method in Comparative Example 1, wherein the infrared hydroxyl spectra of the titanium silicon molecular sieve of Example 1 and Comparative Example 1 are as follows Figure 1 As shown, according to the above data and Figure 1 It can be seen that the titanium silicon molecular sieve prepared by the method provided by the present disclosure has a higher conductivity than the titanium silicon molecular sieve 3740cm -1 and 3500cm -1 The peak intensity of the characteristic peak at the position is lower and the peak area is smaller, indicating that the titanium silicon molecular sieve prepared by the method provided by the present invention has fewer nested hydroxyl groups and terminal hydroxyl groups, indicating that the molecular sieve provided by the present invention has better lipophilicity, is easier to adsorb reactants, and accelerates the reaction rate.
[0189] In addition, compared with Comparative Examples 1 and 2, the NMR silicon spectrum data of the titanium silicon molecular sieve prepared by the method provided by the present disclosure shows less Q 3 Species, the magnetic silicon spectrum of the titanium silicon molecular sieve obtained by the traditional synthesis method in Comparative Example 1 is Q 3 The peak area Q3" at the species spectrum peak (-103ppm) is used as the benchmark. The magnetic silicon spectrum Q 3 The peak area Q3 at the species spectrum peak (-103ppm) is 60-80% of the titanium silicon molecular sieve obtained by the traditional synthesis method in Comparative Example 1. The magnetic silicon spectra of the titanium silicon molecular sieves of Example 1 and Comparative Example 1 are as follows: Figure 2 As shown, according to the above data and Figure 2 It can be seen that the titanium silicon molecular sieve prepared by the method provided by the present disclosure has less Q than the titanium silicon molecular sieve prepared by the traditional method. 3 Species, indicating that the molecular sieve has fewer hydroxyl groups and is more lipophilic.
[0190] Table 2
[0191]
[0192]
[0193] Application test case
[0194] This test example is used to evaluate the performance of the titanium silicon molecular sieve prepared in the comparative example and the example as a catalyst in catalyzing the ammoximation reaction of cyclohexanone. Specifically, it includes the following process:
[0195] The ammoximation reaction of cyclohexanone was carried out in a 250ml three-necked flask reaction device with an automatic temperature-controlled water bath, magnetic stirring and condensation reflux system. The samples prepared in the above embodiments and comparative examples were added into a three-necked flask (the mass ratio of catalyst to cyclohexanone was 0.1) according to the sample amount of 1.00g, 10g (0.14mol) of solvent tert-butyl alcohol, and 9.8g (0.1mol) of cyclohexanone, respectively, and placed in a water bath with a preset reaction temperature of 80°C. A peristaltic pump was used to dropwise add 13.7g (0.12mol) of hydrogen peroxide with a mass fraction of 30% by weight and 28.1g (0.2mol) of ammonia water with a mass fraction of 25% by weight, respectively, wherein the molar ratio of cyclohexanone: ammonia water: hydrogen peroxide: solvent was 1:2:1.2:1.35. The reaction was stopped after 0.5h, the temperature was rapidly lowered, and the liquid product was separated by suction filtration, and the composition was determined. The results are listed in Table 3 below.
[0196] For the long-cycle reaction, 1.00 g of the obtained sample was placed in a 100 mL slurry bed reactor with continuous feeding and membrane separation device, and hydrogen peroxide with a mass fraction of 30% by weight was added at 24.7 mL / h, ammonia with a mass fraction of 25% by weight was added at 61.7 mL / h, and a mixture of cyclohexanone and tert-butanol (cyclohexanone and tert-butanol volume ratio of 1:2) was added at 72.2 mL / h under stirring, and the material was continuously discharged at the same speed. The reaction temperature was maintained at 80 ° C, the reaction was continued for 120 hours, and then sampling and analysis were performed every 12 hours; the data in the column of "Long-cycle reaction results" in Table 3 is the average of 5 sampling results after 120 hours of reaction.
[0197] Cyclohexanone conversion rate (%) = (cyclohexanone mole number in the raw material - cyclohexanone mole number in the product) / cyclohexanone mole number in the raw material × 100%;
[0198] Cyclohexanone oxime selectivity (%) = the number of moles of cyclohexanone oxime generated in the product / the number of moles of cyclohexanone consumed to generate all products × 100%;
[0199] Cyclohexanone conversion rate reduction rate (%) = (0.5h cyclohexanone conversion rate - 120h cyclohexanone conversion rate) / 0.5h cyclohexanone conversion rate × 100%;
[0200] Cyclohexanone oxime selectivity reduction rate (%) = (0.5h cyclohexanone oxime selectivity - 120h cyclohexanone oxime selectivity) / 0.5h cyclohexanone oxime selectivity × 100%.
[0201] The reaction product was analyzed by gas chromatography, and the analysis results were quantified by external standard method. The chromatographic analysis conditions were: Agilent-6890 chromatograph, HP-5 capillary column, injection volume 0.5 μL, injection port temperature 280°C. The column temperature was maintained at 100°C for 2 min, then increased to 250°C at a rate of 15°C / min and maintained for 10 min. FID detector, detector temperature 300°C.
[0202] Table 3
[0203]
[0204]
[0205] According to the data in Tables 1 to 3 above:
[0206] In the comparative example 1, no second template is added during the preparation of the titanium silicalite molecular sieve. In the comparative example 2, no second template is added during the preparation of the titanium silicalite molecular sieve, and no acid treatment and second hydrothermal crystallization treatment are performed. Compared with the titanium silicalite molecular sieves D-1 to D-2 prepared in comparative examples 1 to 2, the titanium silicalite molecular sieves prepared by the method provided in the present disclosure in examples 1 to 15 can obtain higher cyclohexanone conversion rate and cyclohexanone oxime selectivity in the catalytic cyclohexanone ammoximation reaction.
[0207] Compared with Examples 6 to 10, Examples 1 to 5 and 11 to 12 were subjected to acid treatment and a second hydrothermal crystallization treatment during the molecular sieve synthesis process. Compared with the titanium silicon molecular sieve prepared in Examples 6 to 10, the I1 value of the titanium silicon molecular sieve prepared in Examples 1 to 5 and 11 to 12 was within the preferred range of 3.03 to 5.05, and the calculated I0 was within the range of 45 to 75%. The titanium silicon molecular sieve prepared in Examples 1 to 5 and 11 to 12 was able to obtain a higher cyclohexanone conversion rate and cyclohexanone oxime selectivity in the catalytic cyclohexanone ammoximation reaction.
[0208] Comparing Example 1 with Example 13, it can be seen that the amount of raw material added in the synthesis process of the titanium silicalite in Example 1 is within the preferred range of "the molar ratio of silicon source: titanium source: composite template: water is 1: (0.010-0.035): (0.10-0.20): (10-30), and the molar ratio of the first template to the second template is 1: (0.03-0.08)", the amount of raw material added in Example 13 is not within the preferred range, and the total hydroxyl area I1 of the infrared hydroxyl spectrum of the titanium silicalite is not within the range of 3.03-5.05. Compared with the titanium silicalite prepared in Example 13, the titanium silicalite prepared in Example 1 can obtain higher cyclohexanone conversion rate and cyclohexanone oxime selectivity in the catalytic cyclohexanone ammoximation reaction, and the cyclohexanone conversion rate reduction rate and cyclohexanone oxime selectivity reduction rate under long-term reaction conditions are lower, and the stability is better;
[0209] Comparing Example 1 with Example 15, it can be seen that the preparation conditions of Example 1 are within the preferred embodiment range provided in the present disclosure, while Example 15 is not within the preferred range, and the total hydroxyl area I1 of the infrared hydroxyl spectrum of the titanium silicate molecular sieve is not within the range of 3.03 to 5.05. Compared with the titanium silicate molecular sieve prepared in Example 15, the titanium silicate molecular sieve prepared in Example 1 can obtain higher cyclohexanone conversion rate and cyclohexanone oxime selectivity in the catalytic cyclohexanone ammoximation reaction, and the cyclohexanone conversion rate reduction rate and cyclohexanone oxime selectivity reduction rate under long-term reaction conditions are lower, and the stability is better.
[0210] Diffusion test case
[0211] This test example is used to evaluate the hydrophilic and lipophilic properties of the molecular sieves prepared in the examples and comparative examples. Specifically, it includes the following steps:
[0212] The packed column in the gas chromatograph is replaced with a zero-length column filled with the sample to be tested, nitrogen is used as the carrier gas, the flow rate is 10mL / min, and the column box is 200℃ to pretreat the sample for 1h. During the experiment, the temperature is constant at 200℃, and the carrier gas carrying a certain concentration of cyclohexane vapor is passed through the zero-length column. When the signal of the gas chromatograph detector is basically unchanged, the cyclohexane reaches adsorption equilibrium, and this concentration is used as c0. Then the gas flowing through the long column is switched to pure carrier gas, and this moment is used as t0. The diffusion curve is measured and recorded, and the diffusion coefficient of the titanium silicon molecular sieve is obtained according to the curve. The diffusion test results are listed in Table 4 below; the relative diffusion coefficient in Table 4 is the diffusion coefficient of the titanium silicon molecular sieve D-2 prepared in Comparative Example 2 as a comparison benchmark.
[0213] Table 4
[0214]
[0215]
[0216] According to the data in Table 4 above, it can be seen that the diffusion coefficient of the titanium silicate prepared in the embodiment of the present disclosure is high, indicating that cyclohexane has better diffusion performance and better lipophilicity in the titanium silicate prepared in the embodiment of the present disclosure.
[0217] Comparing Examples 1 to 5 and 11 to 12 with Examples 6 to 10, the relative diffusion coefficients of the titanium silicon molecular sieves prepared in Examples 1 to 5 and 11 to 12 are higher, indicating that the titanium silicon molecular sieves prepared by the acid treatment and the second hydrothermal crystallization treatment during the molecular sieve synthesis process have better diffusion performance and better lipophilicity;
[0218] Comparing Example 1 with 13 and 15, it can be seen that the titanium silicalite synthesized in Example 1 according to the preferred raw material addition amount and optimized preparation conditions has a higher relative diffusion coefficient, better diffusion performance and better lipophilicity.
[0219] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0220] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0221] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing titanium silicon molecular sieve, characterized in that: The following steps are involved: S1, contacting a silicon source, a titanium source, a composite template and water to obtain a raw material mixture; wherein the composite template comprises a first template and a second template; the first template is selected from one or more compounds having a structure shown in the following formula (1); the second template is selected from one or more compounds having a structure shown in the following formula (2): In formula (1), R1, R2, R3 and R4 are each independently selected from an alkyl group having 2 to 5 carbon atoms or an alkenyl group having 2 to 5 carbon atoms; In formula (2), R5, R6 and R7 are each independently selected from an alkyl group having 2 to 5 carbon atoms or an alkenyl group having 2 to 5 carbon atoms; R8 is selected from an aryl group having 6 to 12 carbon atoms; S2. subjecting the raw material mixture to a first hydrothermal crystallization treatment.
2. The method according to claim 1, characterized in that In the first template formula (1), R1, R2, R3 and R4 are each independently selected from an alkyl group having 3 carbon atoms or an alkenyl group having 3 carbon atoms; optionally, the first template is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, butyltripropylammonium hydroxide, 1-butenyltripropylammonium hydroxide, 2-butenyltripropylammonium hydroxide and 3-butenyltripropylammonium hydroxide; preferably, it is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, butyltripropylammonium hydroxide and 1-butenyltripropylammonium hydroxide; Optionally, in the second template agent formula (2), R5, R6 and R7 are each independently selected from an alkyl group having 2 to 4 carbon atoms or an alkenyl group having 2 to 4 carbon atoms; R8 is selected from an aryl group having 6 to 8 carbon atoms; preferably, R5, R6 and R7 are each independently selected from an alkyl group having 3 carbon atoms or an alkenyl group having 3 carbon atoms; R8 is selected from a group having 6 to 8 carbon atoms and containing a phenylene group; optionally, the second template agent is selected from phenyl tripropyl ammonium hydroxide, p-tolyl tripropyl ammonium hydroxide, p-ethylphenyl tripropyl ammonium hydroxide, benzyl tripropyl ammonium hydroxide, phenethyl tripropyl ammonium hydroxide, phenyl allyl dipropyl benzene The invention relates to one or more of p-tolyl allyl dipropyl ammonium hydroxide, p-ethylphenyl allyl dipropyl ammonium hydroxide, benzyl allyl dipropyl ammonium hydroxide, phenethyl allyl dipropyl ammonium hydroxide, phenyl allyl dipropyl ammonium hydroxide, p-tolyl allyl dipropyl ammonium hydroxide, p-ethylphenyl allyl dipropyl ammonium hydroxide, benzyl allyl dipropyl ammonium hydroxide and phenethyl allyl dipropyl ammonium hydroxide; preferably, it is one or more selected from phenyl tripropyl ammonium hydroxide, p-tolyl tripropyl ammonium hydroxide, phenyl allyl dipropyl phenyl ammonium hydroxide, benzyl allyl dipropyl ammonium hydroxide and phenyl allyl dipropyl ammonium hydroxide.
3. The method according to claim 1, characterized in that The silicon source is selected from at least one of organic silicone grease, solid silica gel, white carbon black and silica sol; preferably at least one of organic silicone grease, solid silica gel and white carbon black; Optionally, the organic silicone grease is selected from one or more compounds having a structure represented by the following formula (A): R a , R b , R c and R d Each is independently selected from an alkyl group having 1 to 4 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, the R a , R b , R c and R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl; further preferably, the organic silicone grease is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicate; further preferably, it is selected from one or more of tetramethyl silicate, tetraethyl silicate and dimethyl diethyl silicate; Optionally, the titanium source is selected from one or more of an organic titanium source and an inorganic titanium source; Preferably, the organic titanium source is a titanium-containing organic acid ester, selected from at least one of the structures represented by the following formula (B): Where R e , R f , R g and R h are each selected from an alkyl group having 1 to 6 carbon atoms, preferably a straight-chain alkyl group having 1 to 4 carbon atoms and a branched-chain alkyl group having 3 to 6 carbon atoms, and more preferably R e , R f , R g and R h are independently selected from a straight chain alkyl group having 2 to 4 carbon atoms and a branched chain alkyl group having 2 to 4 carbon atoms; optionally, R e , R f , R g and R h Each of the following groups is independently selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl and isohexyl; preferably each of the following groups is independently selected from one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl; Preferably, the inorganic titanium source is selected from one or more of chloride, nitrate or sulfate of titanium; Further preferably, the titanium source is selected from one or more of titanium tetrachloride, titanium sulfate, titanium nitrate, tetraethyl titanate, tetrapropyl titanate and tetrabutyl titanate.
4. The method according to claim 1, characterized in that: In step S1, the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): composite template: water is 1: (0.001-0.040): (0.05-0.30): (5-40); preferably 1: (0.010-0.035): (0.10-0.20): (10-30); Preferably, in the composite template, the molar ratio of the first template to the second template is 1:(0.01-0.10), preferably 1:(0.02-0.08), and more preferably 1:(0.03-0.08).
5. The method according to claim 1, characterized in that Step S1 also includes the step of hydrolyzing and removing alcohol from the raw material mixture; Optionally, the conditions for the hydrolysis and alcohol removal treatment include: treating at 5-120° C. for 0.5-48 h; preferably treating at 50-100° C. for 1-24 h, and more preferably treating at 60-90° C. for 5-20 h.
6. The method according to claim 1, characterized in that In step S2, the conditions of the first hydrothermal crystallization treatment include: a hydrothermal crystallization temperature of 150 to 200°C, a hydrothermal crystallization time of 2 to 168 hours, and a hydrothermal crystallization pressure of autogenous pressure; preferably, the hydrothermal crystallization temperature is 160 to 190°C, and the hydrothermal crystallization time is 4 to 80 hours; further preferably, the hydrothermal crystallization temperature is 165 to 188°C, and the hydrothermal crystallization time is 5 to 40 hours.
7. The method according to claim 1, characterized in that The method further comprises: drying and / or calcining the crystallized product obtained by the first hydrothermal crystallization treatment to obtain a solid product; Optionally, the drying conditions include: a drying temperature of 100 to 200° C. and a drying time of 2 to 10 hours; The conditions for the calcination treatment include: a calcination temperature of 350-650° C. and a calcination time of 2-10 hours; preferably, a calcination temperature of 450-550° C. and a calcination time of 3-8 hours.
8. The method according to claim 7, characterized in that The method further comprises: contacting the solid product with an acid solution to perform an acid solution treatment, and then adding a pH regulator to perform a neutralization treatment to obtain an intermediate product; Optionally, in the acid treatment, the acid is selected from one or more of hydrochloric acid, nitric acid, phosphoric acid, carbonic acid, sulfuric acid and acetic acid; the acid concentration is 0.1-1.0 mol / L, and the mass volume ratio of the acid to the solid product is 80-150 g solid product / 1 L acid; Optionally, the conditions of the acid treatment include: contact temperature of 50-150° C., preferably 60-100° C., contact time of 0.5-5.0 h, preferably 1.0-3.5 h; Optionally, the pH adjuster is selected from one or more alkali solutions; the alkali solution is selected from one or more of ammonia water, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate and sodium bicarbonate, and the neutralization treatment adjusts the pH value of the solution to 5-7.
9. The method according to claim 8, characterized in that The method further comprises: mixing the intermediate product with a third template and performing a second hydrothermal crystallization treatment; Optionally, the mass ratio of the intermediate product to the third template is 2 to 20:1; preferably 5 to 15:1; the conditions of the second hydrothermal crystallization treatment include: a hydrothermal crystallization temperature of 150 to 200°C, a hydrothermal crystallization time of 10 to 40 hours, and a hydrothermal crystallization pressure of autogenous pressure; preferably, the hydrothermal crystallization temperature is 160 to 180°C, and the hydrothermal crystallization time is 20 to 30 hours; Optionally, the third template is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, allyltripropylammonium hydroxide and butyltripropylammonium hydroxide.
10. Titanium silicon molecular sieve prepared according to the method according to any one of claims 1 to 9.
11. A titanium silicon molecular sieve, characterized in that: The titanium silicate molecular sieve has the following infrared hydroxyl spectrum characteristics: The infrared hydroxyl spectrum of the titanium silicalite molecular sieve is 3200-3800 cm -1 The peak area calculated by normalizing the characteristic peak within the wavenumber range is recorded as I1, and I1 is 1.35 to 6.55, preferably any value between 1.35 and 5.38, and more preferably any value between 3.03 and 5.
05.
12. The titanium silicon molecular sieve according to claim 11, characterized in that: The molar ratio of silicon atoms to titanium atoms in the titanium silicon molecular sieve is 10 to 100:1, preferably 20 to 50:1; Optionally, the average particle size of the molecular sieve particles of the titanium silicate molecular sieve is 0.10 to 0.50 μm, preferably 0.20 to 0.40 μm; the BET specific surface area is 400 to 500 m 2 / g, preferably 430 to 470 m 2 / g; micropore specific surface area is 350~450m 2 / g, preferably 380 to 410 m 2 / g; total pore volume is 0.20~0.50cm 3 / g, preferably 0.30 to 0.40 cm 3 / g; mesopore volume is 0.03~0.30cm 3 / g, preferably 0.15 to 0.25 cm 3 / g; Optionally, the titanium silicalite molecular sieve has an AEL, AFI, AFN, BEC, CFI, CHA, CON, EUO, FAU, FER, IMF, LTA, MER, MFI, MEL, MOR, MWW, RHO, TON, *BEA, *EWT or a two-dimensional hexagonal phase structure; preferably, it has an MFI structure.
13. Use of the titanium silicon molecular sieve according to any one of claims 10 to 12 in catalytic organic reaction and / or adsorption separation process.
14. The use according to claim 13, characterized in that The catalytic organic matter reaction includes olefin epoxidation to prepare epoxy compounds, olefin chlorohydrinization to prepare chlorohydrin, aldehyde / ketone ammoximation to prepare aldehyde / ketone oxime and ketone Beckmann rearrangement to prepare amide; Optionally, the organic catalytic reaction is cyclohexanone ammoximation, comprising the following steps: Under oximation reaction conditions, cyclohexanone, an oxidant, ammonia and a catalyst are contacted to carry out an oxidation reaction; the catalyst comprises the titanium silicon molecular sieve; Optionally, the oxidant is selected from one or more of hydrogen peroxide, tert-butyl hydroperoxide, cumene hydroperoxide and m-chloroperbenzoic acid; preferably, the reaction is carried out in the presence of a solvent; the solvent is selected from one or more of n-butanol, tert-butanol, ethanol, methanol and cyclohexanol; Preferably, the oximation reaction conditions include: the molar ratio of the oxidant to cyclohexanone is 1.2 to 2.0:1, the molar ratio of the solvent to cyclohexanone is 0.5 to 5:1, the molar ratio of ammonia to cyclohexanone is 1.0 to 3.0:1, and the weight ratio of the catalyst to cyclohexanone is 0.05 to 0.2:1; the reaction temperature is 60 to 90°C, and the reaction time is 0.3 to 1.0h.
Citation Information
Patent Citations
Lamellar catalyst containing mesoporous titanium-silicate molecular sieves and preparation method and application of lamellar catalyst
CN104437616A
Hierarchical pore titanium silicalite molecular sieve for packaging active metal and preparation method thereof
CN111847471A
Synthesis of Ti-Si ultra macroporous molecular sieve
CN1137023A
Surface-modified silicate titanium silicalite molecular sieve catalyst, preparation method and application of surface-modified silicate titanium silicalite molecular sieve catalyst in epoxidation preparation of epoxy chloropropane
CN116174030A
Epoxidation process using titanium-rich silicalite catalysts
US5262550A